The Impact of Corporate Governance Mechanisms on Strategic Risk Management and Firm Performance - Rahma Nurzianti; Tosi Rahmaddian; Mokhamad Yaurizqika Hadi (Malaqbi Publisher, 2026)
This study investigates the impact of corporate governance mechanisms on strategic risk management (SRM) and firm performance, with SRM examined as a mediating variable. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from managerial-level respondents across firms operating in dynamic and high-risk environments. The results reveal that board independence and board expertise significantly enhance SRM practices, underscoring the role of effective oversight and domain knowledge in shaping strategic responses to risk. SRM is also found to have a strong positive effect on firm performance, demonstrating its strategic value in improving organizational resilience and competitive advantage. However, board independence, board expertise, and board size show no direct effect on firm performance, indicating that governance mechanisms influence outcomes primarily through risk management processes rather than direct governance intervention. Board size also exhibits no significant relationship with SRM, suggesting that capability and functional effectiveness matter more than structural characteristics. Furthermore, SRM significantly mediates the relationships between board independence and firm performance, and between board expertise and firm performance, confirming its role as a crucial conduit through which governance affects organizational results. Overall, the findings reinforce the importance of aligning governance quality with strategic risk practices to enhance firm performance in increasingly unpredictable business environments.